Gender Relations in the Ideology of the Fundamentalist Church of Jesus Christ of Latter-Day Saints (FLDS) in the Documentary Film Keep Sweet: Pray and Obey - Najihah, Bannan Naelin (Asyahid Journal of Islamic and Quranic Studies (AJIQS), 2024)
Isu kesetaraan gender dalam komunitas religius fundamentalis sering kali terkait dengan upaya mempertahankan nilai tradisional di tengah perubahan sosial. Fundamentalist Church of Jesus Christ of Latter-Day Saints (FLDS) adalah contoh di mana gerakan sosial ini mengokohkan patriarki dan membentuk ulang peran gender, dengan membatasi otonomi perempuan melalui narasi keagamaan. Dokumenter Keep Sweet: Pray and Obey menggambarkan bagaimana komunitas FLDS mengendalikan identitas perempuan dengan ajaran ketaatan dan subordinasi, menciptakan struktur sosial yang memperkuat agenda konservatif mereka. Penelitian ini bertujuan untuk menganalisis relasi gender dalam ideologi Fundamentalist Church of Jesus Christ of Latter-Day Saints (FLDS) menggunakan teori R.W. Connell sebagaimana disajikan dalam film dokumenter Keep Sweet: Pray and Obey. Metode yang digunakan adalah kualitatif deskriptif dengan pendekatan analisis wacana, sementara jenis studi yang diterapkan adalah studi pustaka. Hasil penelitian menunjukkan bahwa maskulinitas hegemonik dalam FLDS menciptakan struktur kekuasaan yang memperkuat dominasi laki-laki, memosisikan perempuan dalam subordinasi mutlak. Maskulinitas subordinat dan marginal dalam komunitas ini memperkuat kekuasaan maskulinitas hegemonik dengan mengamankan posisi pria senior, sementara konsep maskulinitas kompilasi memungkinkan laki-laki yang tidak mendominasi sepenuhnya tetap mendapatkan keuntungan sosial. Di sisi lain, norma gender yang ketat menetapkan peran perempuan sebagai istri patuh dan ibu, memperkuat hierarki patriarki dan mengukuhkan posisi subordinat perempuan dalam komunitas FLDS. Pendekatan interseksional dalam penelitian ini juga menunjukkan bahwa perempuan di komunitas ini mengalami bentuk penindasan yang berlapis melalui kombinasi identitas gender, agama, dan status sosial. Kata kunci: FLDS; poligami; patriarki;   Abstract Gender equality issues in fundamentalist religious communities are often linked to maintaining traditional values amidst social change. The Fundamentalist Church of Jesus Christ of Latter-Day Saints (FLDS) is an example of a social movement that reinforces patriarchy and reshapes gender roles by limiting women's autonomy through religious narratives. The documentary Keep Sweet: Pray and Obey illustrates how FLDS communities control women's identities with teachings ofobedience and subordination, creating social structures that reinforce their conservative agenda. This research aims to analyze gender relations in the Fundamentalist Church of Jesus Christ of Latter-Day Saints (FLDS) ideology using R.W. Connell's theory as presented in the documentary Keep Sweet: Pray and Obey. The method used is descriptive qualitative with a discourse analysis approach, while the type of study applied is a literature study.  The results show that hegemonic masculinity in the FLDS creates a power structure that reinforces male dominance, positioning women in absolute subordination. Subordinate and marginal masculinities in this community reinforce the power of hegemonic masculinity by securing the position of senior men, while the concept of compositional masculinity allows men who do not fully dominate to still gain social advantages. On the other hand, strict gender norms stipulate women's roles as obedient wives and mothers, reinforcing patriarchal hierarchies and entrenching women's subordinate positions in FLDS communities. The intersectional approach in this study also shows that women in this community experience multiple forms of oppression through a combination of gender identity, religion and social status. Keywords: FLDS; polygamy; patriarchy;